THE EVALUATION OF EARLY INITIATION BREASTFEEDING PRACTICE in Dr. mohammad hoesin hospital palembang - Bernolian, Nuswil; Sjaaf, Amal C. (Proceedings of the International Conference on Applied Science and Health, 2017)
Background: Compared to other countries, the rate of EIB in Indonesia remains low (34,5%). During our practice, particulary in delivery room, we often find practices which delayed EIB. The recent finding that early initiation of breastfeeding (EIB) could substantially reduce neonatal mortality should result in more comprehensive efforts to increase the number of infants breast-fed within an hour of birth. Such efforts can only be effective if policies and guidelines are based on a solid knowledge of the barriers and facilitators for EIB. Aims: To evaluate EIB practice in Dr. Moh. Hoesin hospital. Methods: This was an analytic observational study, using cross sectional design. Our populations were all of afterbirth mothers (spontaneous or abdominal delivery), doctors, midwifes, as well as managerial policy holder. Samples were selected by purposive sampling. Data was obtained from the questionnaire which have been tested for validity and reliability. This study included 29 doctors and 14 midwifes as EIB implementers; also 12 managerial staffs. Results: During the periodNovember to December 2016, there were 19 (51.3%) patients with post spontaneous or abdominal deliverypracticed EIB and 18 (48.6%) patients did not practice EIB. Most of patients in âno EIB groupâ had abdominal delivery (p = 0,003). Most of patients complained that no EIB policy in operating room. Most of implementers stated that EIB already done well. The EIB implementers complained that there was lack of support about EIB practice from hospital manager and maternal level of knowledge was low. Our study found the disintegration between the managerial and executive staff, causing ambiguity in the practice of the EIB. Conclusion: The opportunitiy of EIB practice was affected by medical condition ofmother and fetus,method of delivery, hospital support, EIB policy socialization, and patientâs knowledge. There were so many challenges for our hospital to practice EIB, such as no EIB policy in operating room,the mothers condition wasnot possible to practice EIB, knowledge of the managerial about EIB differ greatly, low socialization about regulations and other elements of the EIB implementation. Thereis also disintegration between the managerand executive staff causing ambiguity in the practice ofEIBand the lack of supervision of EIB practice in the field.Â